2010
DOI: 10.1080/00268976.2010.523017
|View full text |Cite
|
Sign up to set email alerts
|

A quantum chemical study of the mechanism for proton-coupled electron transfer leading to proton pumping in cytochrome c oxidase

Abstract: The proton pumping mechanism in cytochrome c oxidase, the terminal enzyme in the respiratory chain, has been investigated using hybrid DFT with large chemical models. In previous studies, a gating mechanism was suggested based on electrostatic interpretations of kinetic experiments. The predictions from that analysis are tested here. The main result is that the suggestion of a positively charged transition state for proton transfer is confirmed, while some other suggestions for the gating are not supported. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…One suggestion is that the transition state in the D-channel, where all pumped protons are transferred, has a positive character, which means that it is low when there is an uncompensated electron in the vicinity, such as in the low-spin heme a , thus allowing the proton to be taken up in the first place. But when the electron is neutralized by the proton in the BNC, the barrier is high, and the proton that is expelled from the PLS cannot return to the N-side, and has to go to the P-side ( Siegbahn and Blomberg, 2007 ; Blomberg and Siegbahn, 2010 ; Blomberg and Siegbahn, 2012 ). The positive character of the transition state is achieved by the traveling proton itself, and excludes an initial deprotonation of the glutamic acid at the BNC end of the D-channel.…”
Section: Resultsmentioning
confidence: 99%
“…One suggestion is that the transition state in the D-channel, where all pumped protons are transferred, has a positive character, which means that it is low when there is an uncompensated electron in the vicinity, such as in the low-spin heme a , thus allowing the proton to be taken up in the first place. But when the electron is neutralized by the proton in the BNC, the barrier is high, and the proton that is expelled from the PLS cannot return to the N-side, and has to go to the P-side ( Siegbahn and Blomberg, 2007 ; Blomberg and Siegbahn, 2010 ; Blomberg and Siegbahn, 2012 ). The positive character of the transition state is achieved by the traveling proton itself, and excludes an initial deprotonation of the glutamic acid at the BNC end of the D-channel.…”
Section: Resultsmentioning
confidence: 99%
“…A few DFT calculations have been performed to evaluate certain aspects of the suggested mechanisms. One DFT study used a model of about 250 atoms, including the heme a cofactor, the region around the suggested PLS, the region around the suggested TS G , and a very simplified description of the BNC (essentially only the Cu B ion) . Using this model, it could be shown that the Coulombic effect from an electron in heme a is very similar at the PLS and TS G , which is the basic ingredient in the suggested gating mechanism.…”
Section: Heme Enzymesmentioning
confidence: 99%
“…A combination of electrostatic and large-scale DFT calculations with associated energy analysis has been used to examine the proton-pumping mechanism in class A1 (aa 3 -type) enzymes. ,, In a number of papers, Blomberg and Siegbahn have proposed that 1e – transfer from the Cu A center to the mononuclear heme-a drives protonation at a pump-loading site (PLS) close to a propionate in heme-a 3 , as well as protonation of the glutamate (Glu286 in bacterial Rs and a homologous glutamate in mitochondria). Both protons originate from the D proton channel.…”
Section: Objectives Of the Theoretical/computational Cyclementioning
confidence: 99%